Immediate postpartum family planning utilization and its associated factors among postpartum women in Ethiopia: a systematic review and meta-analysis - Silesh, Mulualem; Demisse, Tesfanesh Lemma; Taye, Birhan Tsegaw; Moltot, Tebabere; Chekole, Moges Sisay; Wogie, Girma; Kasahun, Fetene; Adanew, Solomon (Frontiers in Global Women's Health, 2023)
Background Family planning integration in areas where women contact the healthcare system routinely is essential for addressing the high unmet need for family planning among postpartum women and reducing the risk of short interpregnancies. Immediate postpartum family planning (IPPFP) is an integrated service, and opportunities exist for women by providing family planning (FP) counseling and contraceptives as part of care following childbirth within 48 h. Therefore, this review aimed to assess the pooled estimate of immediate postpartum family planning utilization and its associated factors in Ethiopia. Method Electronic databases were used to conduct an extensive search of all published studies, and the digital library was used to identify any unpublished studies. An observational study that reports the prevalence/magnitude and/or associated factors/predictors/determinants of IPPFP utilization in Ethiopia was included. Data were extracted on the Microsoft Excel spreadsheet and analyzed using STATA Version 11. A random-effects model was applied to determine the pooled prevalence of immediate postpartum family planning utilization with a 95% confidence interval (CI). Inverse variance (I2) was used to identify the presence of heterogeneity, and a funnel plot and Egger's test were used to check the presence of publication bias. Subgroup analysis was conducted based on the sample size, region, and year of study to identify the source of heterogeneity. Result Of 15 primary studies, the overall pooled prevalence of immediate postpartum family planning utilization among postpartum women in Ethiopia was 21.04% (95% CI: 13.08, 29.00). Received counseling on FP [OR: 3.59; 95% CI (1.84, 7.01; P < 0.001), having a positive attitude toward FP [OR: 3.2; 95% CI (1.23, 8.35); P = 0.017], and partner support to use FP [OR: 5.85; 95% CI (1.12, 30.54; P = 0.036) were significant predictors of immediate postpartum family planning utilization. Conclusion Generally, IPPFP utilization in Ethiopia was insufficient. Therefore, to enhance the utilization, integrating FP counseling at all maternal service care points, strengthening community awareness to develop a favorable attitude toward family planning, and promoting partner involvement in family planning counseling are essential. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=239053, identifier: CRD42021239053.